SELECTION OF SUPERIOR CROSSES ON THE BASIS OF PROGENY MEAN IN POTATO - Pande, P C; Luthra, S K.; Singh, B. P; Pandey, S K (Potato Journal, 2013)
Eighty eight crosses were evaluated in F1C1 stage. Based on high progeny mean for plant vigour, tuber yield and late blight resistance, crosses CP1358 x JEX/A-1192, CP1909 x CP2013, JEM/O-30 x JN1197, JI1857 x JN1197, JN1752 x JEX/A-592, JN1752 x JN1197, JX90 x CP2013, Kufri Chipsona-1 x J92111, Kufri Chipsona-1 x Kufri Anand and Kufri Anand x CP3090 were identified as promising for large scale exploitation in potato breeding programme. Selection based on plant vigour, foliage maturity, desirable tuber traits, high family mean tuber yield supplemented with late blight resistance is recommended for developing potato varieties for north-central plains.